Cover Image. Issue 12 (3rd December 2020) - Unknown
Abstract : Pluteus larva of the painted white sea urchin, Lytechinus pictus . From: Embryo, larval, and juvenile staging of Lytechinus pictus from fertilization through sexual maturation ; Katherine T. Nesbit and Amro Hamdoun; DevDyn 249:11, pp. 1334–1346.